Development Financial Institution (DFI) Employees’ Awareness and Perceptions of Anti-Money Laundering (AML) Practices and Cybersecurity Techniques - Thatayaone Mpuchane; Tapiwa Gande (European Scientific Journal, ESJ, 2023)
The purpose of this study was to assess employees’ perceptions of anti-money laundering practices at the National Development Bank in Botswana. The study used a quantitative approach. A population of 84 respondents who are employees of a development financial institution (DFI), the National Development Bank (NDB) of Botswana was sampled in this study. Out of these, 36 respondents were selected through a stratified random sampling method to ensure representation in all strata. A self-administered questionnaire was used to collect data.  The study found that employees of National Development Bank understand the concept of money laundering and the stages involved in money laundering. Secondly, the study established that the main causes of money laundering were corruption, politicians and prominent person’s influence, and weak banking and financial systems. Thirdly, the study established that money laundering is harmful to the economy in different ways that include increased national crime, increased corruption, and negative effects on the economy. The study recommended that the management of NDB should adopt anti-money laundering/ combating/ counter-terrorism financing (AML/CFT) regulations laid out by regulating bodies including those of the Financial Action Task Force (FATF), Bank of Botswana and the Financial Intelligence Agency (FIA). In addition to this, the bank management should expose its employee to continuous knowledge of ML/FT through in-house training and external workshops with other industry stakeholders. The bank should also adopt a robust record management system that is able to capture all transactions taking place within it. The system should be robust enough to flag suspicious ML/FT activities taking place through transactions carried out within the bank.